Long-term Patterns of Eelgrass (Zostera marina) Occurrence and Associated Herbivorous Waterbirds in a Danish Coastal Inlet - Balsby, Thorsten J. S.; Clausen, Preben; Krause-Jensen, Dorte; Carstensen, Jacob; Madsen, Jesper (Frontiers in Marine Science, 2017)
Seagrasses in coastal areas have substantial importance for the marine environment and also serve as food for herbivorous waterbirds. We investigated potential relationships between the autumn population of herbivorous waterbirds and eelgrass (Zostera marina) abundance in the EU protected area, Nibe-Gjøl Bredning, a broad of the Limfjorden estuarine complex in Denmark.This is an important site for migratory herbivorous waterbirds such as mute swan (Cygnus olor), coot (Fulica atra), brent goose (Branta bernicla), and wigeon (Anas penelope). We explored long-term (27 yr) changes in eelgrass and bird-populations and relationships between eelgrass- and bird abundance. We applied trend- and correlative analyses of yearly monitoring data on eelgrass and waterbirds between 1989 and 2015 coupled with estimates of the potential grazing pressure exerted by the birds. Around 1990 eelgrass was abundant in this area covering more than 40 km2, but eelgrass coverage and biomass declined drastically around 1995 and remained low until 2011 when natural recolonization accelerated and by 2015 had restored the lost meadows. The number of herbivorous waterbirds also fluctuated substantially during the monitoring period with large abundance until the mid-end 1990s followed by reduced abundance in the 2000s and recovery after 2010. The number of bird-days showed a positive relationship with the same year’s eelgrass abundance in the 1-2 m depth stratum. For the 0-1 m depth stratum, where the eelgrass meadows are most exposed to bird grazing but also to physical control from e.g. wind and ice, only a particularly detailed eelgrass data set available for a subset of the study period, showed a significant relationship with bird grazing. The potential waterbird consumption of eelgrass, estimated by multiplying average intake rate and number of bird-days for each species, ranged from less than 16 % of the eelgrass biomass in most years to more than 40 % of the eelgrass biomass in years with extremely sparse eelgrass populations. Hence, the study suggests that dense eelgrass populations stimulate herbivorous waterbirds whereas top-down control is only likely when abundant bird populations graze on sparse eelgrass populations.